EVALUATION THE EFFECT OF TRACTOR SPEEDS AND TILLAGE DEPTHS ON SOME TECHNICAL INDICATORS FOR PLOW LOCALLY MANUFACTURED - & Taha, Taha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research was conducted at the field of Al-Mussaib technical institute dating April 2018, to study effect of tractor speeds and tillage depths on some technical indicators for plow locally manufactured, by using (New Holland TD5) tractor and (Massey Ferguson 375) tractor with combined plow locally manufactured in the various tillage depths as well as effect of tractor speeds in clay loam soil. This research was studied two factors: included three tillage depths (15, 20 and 24 cm). Moreover three practical speeds of the tractor (3.77, 5.19 and 6.45 km·hr-1), the experiment was applied using factorial experiment according to the (CRD) with four replications. The results showed the                  following: increasing tillage depth from 15 to 20 and 24 cm caused an increasing in pulling force, drawbar power and soil volume disturbed, and decrease in the practical productivity. Tillage depth 15 cm indicated significant superiority up on tillage depths 20 and 24 cm achieved lower pulling force, drawbar power, while tillage depth 24 cm achieved higher soil volume disturbed and practical productivity. Increasing practical speeds of tractor from 3.77 to 5.19 and 6.45 km·hr-1 caused an increasing in pulling force, drawbar power, soil volume disturbed and practical productivity. The practical speed of tractor 3.77 km·hr-1 indicated significant superiority up on practical speeds of tractor 5.19 and 6.45 km·hr-1 achieved lower pulling force, drawbar power, while the practical speed of tractor 6.45 km·hr-1 achieved higher soil volume disturbed and higher practical productivity._